FACTORS AFFECTING DESIRE TO BUY ENVIRONMENTAL FRIENDLY PRODUCTS - Judianto Hasan; Hartoyo .; Ujang Sumarwan; Budi Suharjo (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
This research examines factors which are mentioned in various literatures to have influence on desire to buy environmental friendly products. The factors are perceived attributes, personal characteristics and external factors. In this study the factors are put into a model which follows through awareness, interest and desire to buy and was also further analyze. Analysis was carried out using Structural Equation Modelling. This research found that external factor have influenced the desire to buy environmental friendly product. This factor is much more important than that of personal characteristic and perceived attributes.